Corporate Governance Ratings and Firm Value: Empirical Evidence from the Bucharest Stock Exchange - Gherghina, Stefan Cristian (International Journal of Economics and Financial Issues, 2014)
This paper aims at assessing corporate governance by the instrumentality of ratings for a sample of 68 companies listed on the Bucharest Stock Exchange (BSE) over the year 2011. Therewith, current research has the goal of investigating the empirical relationship between the corporate governance ratings and firm value. There were considered both accounting-based firm value measures (return on assets, ROA, as well as return on equity, ROE) and market-based firm value measures (earnings per share, EPS), all being industry-adjusted. The novelty of this study is emphasized by the corporate governance ratings developed for the companies listed on the BSE by using multidimensional data analysis techniques, namely principal component analysis (PCA). By employing PCA for a suite of seven variables (the sum of holdings corresponding to the first three shareholders, the number of shareholders having holdings over 5%, board size, the number of independent directors, the number of non-executive directors, the number of women on board, and CEO duality) there ensued three specific ratings (board independence rating, ownership concentration rating, and board diversity rating), alongside a global rating. Subsequently, by estimating multivariate linear regression models, there was noticed the lack of a statistically significant relationship between the governance global rating and firm value as proxied by ROA, ROE, and EPS, all being industry-adjusted. The lack of a statistically significant relationship was reinforced also for the specific governance ratings. The utility of current research is underlined by the information related to governance ratings towards investors globally, thus being supported the investment decision making. Keywords: corporate governance ratings; firm value; principal component analysis; multivariate linear regression models JEL Classifications: C38; G32; G34